Primary Hyperparathyroidism and Hyperthyroidism Associated with Myotonic Dystrophy: A Review of the Literature - Cherif, Yosra; Zantour, Baha; Alaya, Wafa; Berriche, Olfa; Younes, Samia; Sfar, Mohamed Habib (New Horizons in Medicine and Medical Research Vol. 9, 2022)
Background: Various endocrine manifestations are commonly described in myotonic dystrophy (MD), including primary hypogonadism, diabetes mellitus, and thyroid and parathyroid dysfunction. Aim: The aim of this study is to present a rare case of primary hyperparathyroidism and hyperthyroidism associated with MD as well as to assess its relevance by reviewing the literature. Case Report: We describe a 46-year-old woman with a family history of MD with her son. She was diagnosed with heart arrhythmia and had to have a pacemaker implanted. A bilateral cataract was discovered in her eyes. Muscle weakness, widespread myalgia, and palpitation were among her complaints. Myotonic discharges were seen on electromyography (EMG). Laboratory tests showed high serum calcium 2.83 mmol/L, serum phosphate 1.2 mmol/L, parathormone 362.5 pg/mL, thyroid stimulating hormone TSH 0.02 mIU/L (normal range: 0.34–5.6 mIU/L), FT4 21.17 ng/mL, and negative anti- thyroperoxidase antibodies. A multinodular goiter was discovered during a cervical ultrasound. A lower right parathyroid adenoma was discovered using 99mTc-MIBI scintigraphy. MD related with hyperthyroidism and primary hyperparathyroidism was strongly suggested by the clinical data, family history of MD, EMG data, and endocrine problems. Conclusion: Coexistence of hyperthyroidism and primary hyperparathyroidism in MD may be more prevalent than what was previously recognized. Further studies are needed to establish the link between these disorders and to introduce a standard approach to its diagnosis and management.